1962
DOI: 10.1093/ajcn/11.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Nutritional Status of Alaskan Eskimos

Abstract: The present study was undertaken to investigate this question and to consider the necessity of remedial action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1967
1967
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Vitamin C values have been reported previously for several Inuit TF (Hoygaard, 1941;Rodahl, 1950;Hjarde et al, 1952;Brown, 1954;Heller and Scott, 1967;Mann et al, 1962;Hoffman et al, 1967;Hoppner et al, 1978;Geraci and Smith, 1979;Helms, 1985). Unfortunately, the location of harvest, species, sample size, storage methods and proximate composition values were not routinely given.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Vitamin C values have been reported previously for several Inuit TF (Hoygaard, 1941;Rodahl, 1950;Hjarde et al, 1952;Brown, 1954;Heller and Scott, 1967;Mann et al, 1962;Hoffman et al, 1967;Hoppner et al, 1978;Geraci and Smith, 1979;Helms, 1985). Unfortunately, the location of harvest, species, sample size, storage methods and proximate composition values were not routinely given.…”
Section: Introductionsupporting
confidence: 68%
“…Levels of vitamin C in blueberries (Vaccinium uliginosum) were considerably higher with an average value of 26.20 mg/100 g with a CV between replicates of 18%. Previous published analyses of Vaccinium vitis-idaea (Rodahl, 1950;Hjarde et al, 1952;Brown, 1954;Mann et al, 1962) and Empetrum nigrum (Hoygaard, 1941;Brown, 1954;Hoffman et al, 1967;Kuhnlein, 1989) reported a range of vitamin C between 17-108 and 9-51 mg/100 g, respectively. The values reported here indicate a significantly lower level.…”
Section: Vitamin Cfplant Sourcesmentioning
confidence: 97%
See 3 more Smart Citations